2013
DOI: 10.1037/a0030564
|View full text |Cite
|
Sign up to set email alerts
|

A two-factor model of ethnic identity exploration: Implications for identity coherence and well-being.

Abstract: The purpose of this cross-sectional study was to investigate the multidimensional nature of ethnic identity exploration and its relevance for a broader sense of identity and well-being. Participants were 3,637 ethnic minority college students who completed survey measures of ethnic identity exploration, general identity coherence, general identity confusion, and well-being. Consistent with our 3 hypotheses, the results indicated that (a) ethnic identity exploration comprised 2 dimensions, participation and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(144 citation statements)
references
References 71 publications
12
131
1
Order By: Relevance
“…The development and achievement of a coherent sense of identity has been purported to be associated with adaptive functioning in adolescence, paving the way to subsequent successful transition to adulthood. Hence, it may be tenable that a coherent sense of personal identity would help to guide and protect Hispanic immigrants during the process of acculturation and cultural adaptation (Schwartz et al 2006;Syed et al 2013).…”
Section: Identity Development and Immigrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and achievement of a coherent sense of identity has been purported to be associated with adaptive functioning in adolescence, paving the way to subsequent successful transition to adulthood. Hence, it may be tenable that a coherent sense of personal identity would help to guide and protect Hispanic immigrants during the process of acculturation and cultural adaptation (Schwartz et al 2006;Syed et al 2013).…”
Section: Identity Development and Immigrationmentioning
confidence: 99%
“…This is especially true for children and adolescents, who must attend formal schooling in the society of settlement while remaining faithful to the language and cultural values of their country of origin in the family home. Thus, it is conceivable that difficulties in negotiating the demands from the two cultures can lead to lack of identity coherence and increased identity confusion and distress (Syed et al 2013). Indeed, identity confusion has been strongly associated with emotional distress (i.e., depressive symptoms) and with an increased likelihood of initiating alcohol use in early to mid-adolescence among Hispanic immigrant youth (Donovan et al 2012;Schwartz et al 2008).…”
Section: Identity Development and Immigrationmentioning
confidence: 99%
“…This discussion is still ongoing. For example, in a well-conducted study, Syed et al [2013] suggested that ethnic identity exploration consists of two dimensions: participation and search. Ong, Fuller-Rowell, and Phinney [2010] referred to Phinney and Ong's [2007] revised MEIM scale (MEIM-R) as evidence for a two-factor model.…”
Section: A Brief History Of the Ethnicity Construct And Its Current Umentioning
confidence: 99%
“…Specifically, students who exhibited these characteristics demonstrated higher PA and NA, and provided mixed reports of physical health, showing evidence of higher reports of both good and poor health over the previous month. Similarly, another recent study found that active engagement with ethnic identity was related to positive reports of well-being, whereas ambivalent attempts to learn about one's ethnic identity were negatively related (Syed et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…One recent study suggested that the relation between ethnic identity and well-being is complex. In a large sample of ethnic minority college students, Syed et al (2013) found that engaged participation in activities that contribute to one's ethnic identity development was positively related to well-being, whereas more ambivalent attempts to learn about one's ethnic identity were negatively related.…”
Section: Subjective Well-being (Swb) and Health Among People Of Colormentioning
confidence: 98%